What Causing Them To Be Anxious? : A Study in An English-Speaking Class in West Papua - Misnariah Idrus; Nur Wahidah; Suharmoko; Miftahulfadlik Dabamona (Qalam : Jurnal Ilmu Kependidikan, 2022)
This research was motivated by problems that occurred in English subjects class in a school in West Papua, Indonesia, about students’ anxiety when they spoke using the language they were learning. We focused on identifying characteristics indicating the anxiety and causes of the condition. Therefore, we employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. Characteristics indicating the emergence of anxiety in students are divided into three categories, physical, behavioral, and cognitive. Then, we also found three groups of factors causing speaking anxiety: Communication concerns, Test anxiety, and Fear of Negative Evaluation. Keywords: Speaking anxiety, English, Characteristics, Factors.